'God has had Mercy on Me': Theology and Soteriology in Philo of Alexandria's de Sacrificiis Abelis et Caini. (20th November 2021) - Mackie, Scott D
Abstract: Philo of Alexandria's treatise De sacrificiis Abelis et Caini offers a rich example of his theology and soteriology. The majestic God of De sacrificiis is transcendent, omnipresent, and absolutely unique. Anthropomorphic and anthropopathic conceptions of God also are memorably discussed and dismissed. Standing in tension with these ontological characteristics are relational attributes of God, which often are expressed in redemptive acts. Thus, the merciful God of De sacrificiis 'transcends his transcendence', and compassionately reaches out to humans in need. A full array of soteriological themes populate the pages of the treatise, including the war against the passions, the allegory of the soul, transformative revelatory experiences, salvific worship, contemplative ascent, and the vision of God. Furthermore, the agential acts and roles played by God and humans are complexly intertwined, demonstrating a sophisticated, experientially informed soteriology. Though these important Philonic themes typically are interpreted thematically and systemically, thus 'ironing out' any idiosyncrasies, this essay closely attends to the particular thought of this treatise. As a consequence, unique elements and emphases emerge, which in addition to distinctive depictions of divine compassion and soteriological agency, include a Stoic emphasis on reason, the relative absence of mediatorial figures, and a rare portrayal of an unequivocal visio Dei .